Efficient Super Broadband NIR Ca2LuZr2Al3O12:Cr3+,Yb3+ Garnet Phosphor for pc‐LED Light Source toward NIR Spectroscopy Applications - He, Shuai; Zhang, Liangliang; Wu, Hao; Wu, Huajun; Pan, Guohui; Hao, Zhendong; Zhang, Xia; Zhang, Ligong; Zhang, Hong; Zhang, Jiahua (Advanced optical materials, 2020)
Super broadband near‐infrared (NIR) phosphor converted light‐emitting diodes (pc‐LEDs) are future light sources in NIR spectroscopy applications such as food testing. At present, a few blue LED excitable super broadband NIR phosphors (bandwidth > 300 nm) have been developed producing the NIR output powers below 26 mW at 100 mA input current after LED packaging. Here, an efficient super broadband NIR phosphor achieved by doping Yb3+ is reported in the NIR Ca2LuZr2Al3O12:Cr3+ (CLZA:Cr3+) garnet phosphor developed previously. Benefited from the superposition of Cr3+ emission and highly efficient Yb3+ emission excited by energy transfer from Cr3+, the codoped CLZA:Cr3+,Yb3+ phosphor shows a bandwidth of 320 nm and an internal quantum efficiency of 77.2% both higher than that (150 nm and 69.1%) of singly doped CLZA:Cr3+ phosphor. The codoped phosphor converts LED produced 41.8 mW NIR output at 100 mA input current. The pc‐LED as a light source is also well applied to the NIR transmission spectra measurement of water. The results indicate the great potential of CLZA:Cr3+,Yb3+ phosphor in super broadband NIR pc‐LED applications. Emission band extension with efficiency enhancement of Ca2LuZr2Al3O12:Cr3+ garnet phosphor is achieved via codoping with highly efficient emitting Yb3+. Meanwhile, addition of Yb3+ substantially suppresses luminescence thermal quenching due to the competition between energy transfer and thermal de‐excitation in Cr3+ emittingstates. The results indicate the great potential of Ca2LuZr2Al3O12:Cr3+,Yb3+ phosphors in super broadband near‐infrared phosphor converted light‐emitting diode applications.